Students’ Readiness toward English Learning Post Covid-19 Pandemic in SMPN 6 Singaraja - Dandy Wijaya; Yudha Paramartha (Journal of Psychology and Instruction, 2023)
Student readiness is one aspect that needs to be considered before the learning process begins. Many researchers analyzed student readiness in learning, but unfortunately, only a few researches that checked how students’ learning readiness is in the post-pandemic covid-19. This research was conducted to find out the students' readiness toward English learning in post-pandemic covid-19. The researcher used a quantitative research and used questionnaire to collected the data. The participants of this study were 145 students The quantitative data were analyzed using descriptive analysis about the central tendency of the data. The study showed that the students had the readiness to face new learning situations in post-pandemic Covid-19 in learning English, but were not fully prepared. Based on the results, it is known that students are still not fully prepared in their cognitive readiness section due to a lack of students' understanding of common languages in learning English. Further research is recommended to research related to how to improve students' abilities, especially in the vocabulary mastery section in the post-pandemic covid-19.